Endobronchial lung volume reduction with valves reduces exacerbations in severe emphysema patients - Brock, Judith; Böhmker, Felix; Schuster, Paul Ulrich; Eberhardt, Ralf; Gompelmann, Daniela; Kontogianni, Konstantina; Dittrich, A. Susanne; Benjamin, Nicola; Herth, Felix (Respiratory medicine, 2023)
Background and objective - Exacerbations drive the progression of chronic obstructive pulmonary disease (COPD). Endoscopic lung volume reduction (ELVR) with valves is an established treatment option for patients with severe emphysema. Post-interventional exacerbations are observed in 8-17% of cases. Whether the exacerbation rate changes in the medium term after ELVR, is not known. - Methods - This is a single-center retrospective analysis of severe emphysema patients with endobronchial valve implantation. The number of exacerbations before and after ELVR was compared, including lung function parameters, exercise capacity and degree of lung volume reduction. The primary endpoint of the study was the number of exacerbations one year after ELVR compared to one year before ELVR. - Results - 129 patients (mean age 64.1 ± 7.7 years, 57% female, mean FEV1 0.8 ± 0.2 l, mean RV 243.4 ± 54.9 %) with ELVR in the years 2016-2019 and complete exacerbation history were analyzed. Patients experienced a mean of 2.5 ± 2.2 moderate and severe exacerbations in the year before ELVR. The number of exacerbations decreased significantly to 1.8 ± 2.2 exacerbations in the first year after ELVR (p = 0.009). The decrease in exacerbation rate was associated with the development of complete lobar atelectasis (r = 0.228. p = 0.009). Accordingly, in 41 patients with complete lobar atelectasis, the decrease in exacerbation rate was higher from 2.8 ± 2.0 to 1.4 ± 1.8 exacerbations (p < 0.001). - Conclusions - ELVR with valves appears promising to reduce the exacerbation rate in COPD patients, especially when the full treatment benefit of complete lobar atelectasis is achieved.
Gesehen am 10.06.2024